Efektivitas Home Exercise Pada Kasus Tendinitis Patellaris di Klinik Sport Injury Life : Case Report - Farid Rahman; Hakny Kusuma; Ardhita Hilwa Zakia; Bulan Febri Putri Aristiawati (Joong-Ki : Jurnal Pengabdian Masyarakat, 2024)
Patellar tendinitis is a chronic inflammation that attacks the patellar tendon with continuous, repetitive activity and excessive load on the tendon. In cases of patellar tendinitis the quadriceps muscle is the muscle that is likely to experience tension. The interventions given in cases of patellar tendinitis are ultrasound, cold compresses, massage, exercise, TENS, and tapping. The aim of providing treatment is to reduce pain, swelling, increase joint range of motion, and return to sports activities. Measurements were carried out using midline, Visual Analogue Scale, goniometer, and Manual Muscle Testing. After treatment for 3 weeks, significant results were obtained in reducing pain, swelling, increasing joint range of motion, and being able to return to active living (ADL).